Investigating body perception of multiple virtual hands in synchronized and asynchronized conditions - Mashiyama, Yuki; Kondo, Ryota; Fukuoka, Masaaki; Teo, Theophilus; Sugimoto, Maki (Frontiers in Virtual Reality, 2024)
As part of research on human augmentation, multiple bodies are used in a virtual environment.For example, a study on multiple partial body parts has been conducted using up to 64 hands and showed that multiple hands reduced the distance traveled by one hand. However, body perception has yet to be verified. In this study, we investigated how body perception changes when nine hands, partial bodies, are moved synchronously in a virtual environment, compared to a single hand. In addition, we examined whether the sense of body ownership for all nine hands was elicited simultaneously or whether it was elicited for some of the hands while switching between them. Participants performed a reaching task using one or nine hands presented in a virtual environment. After the reaching task, a threat stimulus was given, and hand movements in response to the threat were measured. After completion of each condition, the subjective sense of body ownership and sense of agency was investigated using a Likert scale. The results indicated that users felt the sense of body ownership of several hands for the nine hands and manipulated them by switching their attention to multiple bodies.